2006
DOI: 10.1002/cphc.200600080
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Simulation of the Photoreaction of a Capped Azobenzene: The Rotational Pathway is Feasible

Abstract: We present first‐principles molecular dynamics simulations of azobenzene and a sterically hindered derivative in the first excited state. The restricted open‐shell Kohn–Sham (ROKS) approach is employed to describe the motion in the lowest excited state. The rotational pathway is observed in the molecular dynamics simulations for both azobenzene and its azacrown ether capped derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…E-mail: nikos.doltsinis@wwu.de. a double bond adjacent to a single bond 40,41 and is in line with previous proposals for rotation-restricted AB derivatives 42,43 and related systems. 44,45 Note that the plane containing the CNNC unit is rotated by 90 • upon E↔Z isomerization, similar to findings for the rhodopsin chromophore.…”
Section: Introductionsupporting
confidence: 91%
“…E-mail: nikos.doltsinis@wwu.de. a double bond adjacent to a single bond 40,41 and is in line with previous proposals for rotation-restricted AB derivatives 42,43 and related systems. 44,45 Note that the plane containing the CNNC unit is rotated by 90 • upon E↔Z isomerization, similar to findings for the rhodopsin chromophore.…”
Section: Introductionsupporting
confidence: 91%
“…27,28,30,31,42,58 On-the-fly dynamics simulations were also performed for the photoisomerization of azobenzene on the basis of semiempirical molecular orbital calculations with the surface hopping method 29,33,55,59,61 and with the multiple spawning method. 32 Recently, ab initio molecular dynamics (AIMD) simulations at the CASSCF level 26,47,54,57 and Car-Parrinello molecular dynamics simulations 34,45,49,50 were also performed for the photoisomerization of azobenzene in nπ * excitation. In our surface hopping AIMD simulation 47 at the state-averaged CASSCF (SA-CASSCF) level, it was shown that cis to trans isomerization in nπ * excitation occurs via two-step rotation mechanism, accompanying rotations of the central NN part and two phenyl rings, and this process can be classified into two types with respect to the orientation of the rotation, namely, clockwise and counterclockwise rotation pathways; the calculated quantum yields and lifetime in the excited states are in very good agreement with the corresponding experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…With restricted open-shell KohnSham ͑ROKS͒ theory 6,7 this approach has been extended to the simulation of photoreactions. [8][9][10][11] In this field on-the-fly simulations are particularly useful because the motion of the nuclei can be modeled for all degrees of freedom. The dynamics of the relaxation from the Franck-Condon regioncorresponding to an excited state system with approximately ground state geometry-to the minimum of the excited state can be simulated.…”
Section: Introductionmentioning
confidence: 99%